RELAKSASI BENSON DAN TERAPI MUROTTAL SURAT AR-RAHMAAN MENURUNKAN KADAR GLUKOSA DARAH PUASA PADA PENDERITA DIABETES MELITUS TIPE 2 DI KECAMATAN MAOS - Purwasih, Esti Oktaviani; Permana, Iman; Primanda, Yanuar (Jurnal Ilmiah Kesehatan Keperawatan, 2017)
Uncontrolled diabetes might generate the physical and psychological complication. The objective of this study was to analyze the effect of Bensonâ€™s relaxation and murottal â€œAr-Rahmaanâ€ to the fasting blood glucose (FBG) and stress score. This research was quasi experimental study with two group pre test-post test control group design. The research has been doneÂ  in the Health Care Center of Maos and â€œGraha Amanahâ€ Clinic of Maos. Sample technique used total sampling, with 60 according to the inclusion criteria. The respondents were divided into control group and intervention group. Every group had 30 respondents. The intervention group was given Bensonâ€™s relaxation and murottal, menwhile the control group was given the Bensonâ€™s relaxation only. This intervention was done twice a day, in the morning and in the afternoon, for 7 days.The results showed the difference of the FBG level before and after intervention between groups (p value=0,000; Z score=- 4,097;Mean+SD intervention group= -66,300+45,672;Mean+SD control group= -23,766+13,438). Bensonâ€™s relaxation and murottal therapy could decrease FBGÂ  significantly.